영유아 교원을 위한 저작권 교육 프로그램 개발 - 오은순(Eun-Soon Oh); 이소현(So-Hyun Lee) (디지털콘텐츠학회논문지, 2017)
본 연구는 영유아교육기관의 원장과 교사들을 대상으로 저작권 교육 프로그램을 개발하는데 그 목적이 있다. 저작권 교육 프로그램은 영유아 교원의 지식실태를 바탕으로 저작권 교육의 요구와 전문가 의견을 반영하여 개발하였다. 프로그램(안)은 영유아교육기관에서 교사와 원장을 대상으로 교육을 실행한 후 개방형 질문지와 심층면담을 통해서 전반적인 평가가 이루어졌다. 프로그램(안)은 평가를 통해 수정보완하여 ‘영유아교원을 위한 저작권 교육 프로그램’이 완성되었다. 프로그램은 교육목적, 교육목표, 교육내용, 교육방법, 운영방법, 교육평가로 구성되었으며, 교육내용은 영유아교육기관에서의 사례를 통해 전달하고자 하였다. The purpose of this study is to develop a copyright education program for the directors and teachers in kindergartens and day care centers. In this study, these programs were developed based on the actual situation of knowledge, copyright education requirements, and professional opinions. In this way, a copyright education programs were designed. Through the program, the directors and teachers were trained on the subject. Then, the overall evaluation was carried out through an open questionnaire and in-depth interview. Through this evaluation, the program was modified. These programs were made up of education purposes, education objectives, education contents, education methods, operating methods, and education evaluation. Education content was intended to be educated through examples from kindergartens and day care centers. KCI Citation Count: 2